A moisture budget perspective of the amount effect. Issue 4 (22nd February 2014) - Moore, M.; Kuang, Z.; Blossey, P. N.
<x xml:space="preserve">Abstract</x> A stable water isotopologue‐enabled cloud‐resolving model was used to investigate the cause of the amount effect on the seasonal (or longer) time scales. When the total water (vapor and condensed phase) budget of the precipitating column of air is considered, our results indicate that as convection becomes stronger and the precipitation rate increases, the δD of precipitation (δDp) depends on the isotopic composition of the converged vapor more than that of surface evaporation. Tests with disabled fractionation from rain evaporation demonstrate that this mechanism does not account for the amount effect as has been previously suggested. If the isotopic content of converged vapor is made uniform with height with a value characteristic of surface evaporation, the amount effect largely disappears, further supporting the dominance of converged vapor in changes to the δDp signal with increasing precipitation. δDp values were compared to the water budget term <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0cq1xz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />EP</alternatives>, where P is precipitation and E is evaporation. Results from this comparison support the overall conclusion that moisture convergence is central in determining the value of δDp and the strength of the amount effect in steady state.